1998
DOI: 10.1007/s11746-998-0170-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of physical and chemical properties of milk fat fractions obtained by two processing technologies

Abstract: Milk fat fractions from supercritical carbon dioxide (SC-CO 2 ) extraction were compared with commercial melt crystallization (MC) fractions for their physical and chemical properties. The fractions were analyzed for fatty acids, triacylglycerols, cholesterol, total carotenoid content, and volatile compounds. The fractions were also evaluated for solid fat content (SFC) by pulsed nuclear magnetic resonance and thermal profiles by differential scanning calorimeter (DSC). The distribution of fatty acids and tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 16 publications
7
13
0
Order By: Relevance
“…Consequently, intermediate and higher molecular weight FAs commence migration into the supercritical phase (Arul et al, 1987). FAs composition trend found in this study was similar to that found in other researches (Hammam et al, 1991;Chen et al, 1992;Lim & Rizvi, 1995;Bhaskar et al, 1998).…”
Section: Fa Compositionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consequently, intermediate and higher molecular weight FAs commence migration into the supercritical phase (Arul et al, 1987). FAs composition trend found in this study was similar to that found in other researches (Hammam et al, 1991;Chen et al, 1992;Lim & Rizvi, 1995;Bhaskar et al, 1998).…”
Section: Fa Compositionsupporting
confidence: 89%
“…Although much research has been carried out with SFE of bovine milk fat (Kankare, Antila, Harvala, & Komppa, 1989;Hammam, Soderberg, & Sivik, 1991;Chen, Schwartz, & Spanos, 1992;Arul, Tardif, Boudreau, McGinnis, & Lencki, 1994;Lim & Rizvi, 1995;Bhaskar, Rizvi, Bertoli, Fay, & Hug, 1998) on buffalo milk fat. The objective of this study is to fractionate buffalo butter oil (BO) into fractions differing from one another in their physicochemical and nutritional characteristics through application of SFE technology.…”
Section: Introductionmentioning
confidence: 99%
“…Fractionation is one of the modification processes to prepare fractions having diversified applications. Fractionation and applications of various fractions of milk fat and their blends in different foods have been reported and reviewed in the literature [5][6][7][8][9][10][11][12][13][14][15][16]. Hartel [5] suggested that the most common technique of milk fat fractionation is dry fractionation.…”
Section: Introductionmentioning
confidence: 99%
“…The alterations in fatty acids and triglyceride components of the fractions compared to the original milk fat are also quite extensively recorded in the literature (8)(9)(10)(11)(12). Dry fractionation of milk fat is a common technique to produce fat fractions with properties and compositions that are suitable for food products.…”
mentioning
confidence: 99%